Chemistry Education University of Mulawarman - Muhammad Iksan (PROSIDING SEMINAR KIMIA, 2015)
Research has been done on the Virtual Labs as a limited means of chemical laboratories in schools, this study aims to determine how much student motivation in the material titration using a virtual lab. In the acid-base titration study using virtual labs can motivate students more enthusiastic in learning teaching activities. The result is obtained after a study conducted using virtual labs and data obtained from the questionnaire and interview. After doing learning with virtual labs can be concluded motivation of students categorized as very high.